Configuration of Primary and Recurrent Aggressive Fibromatosis on Contrast-Enhanced MRI with an Evaluation of Potential Risk Factors for Recurrences in MRI Follow-Up - Sedaghat, Sam; Surov, Alexey; Krohn, Sebastian; Sedaghat, Maya; Reichardt, Benjamin; Nicolas, Volkmar (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To analyze the appearance of primary and recurrent aggressive fibromatosis (AF) on MRI with a focus on configuration and to determine potential risk factors for recurrences detected on MRI follow-up scans.Methods From 79 consecutive patients with histologically proven diagnosis of AF, 39 patients underwent a minimum of four 1.5 T MRI follow-up scans after resection of primary AF between 2008 and 2018. The primary and recurrent tumors were radiographically examined for configuration, limitation and extent on MRI. Epidemiological data and loco-regional subcutaneous edema, muscle edema and post-operative seroma were included.Results The mean age of the patients was 39 ± 2.6 years. Primary and recurrent AF most often occurred in the thigh. The main appearance of primary AF was significantly most often fascicular (p = 0.001–0.01) with heterogeneous and marked contrast enhancement. 21 % (n = 8) of the patients developed recurrences of AF. A fascicular configuration with homogeneous/heterogeneous contrast enhancement was the main appearance of recurrent AF, but recurrent AF appeared nodular, polycyclic, ovoid or streaky/flat as well. Recurrent AF significantly most often occurred within the first 9 months after primary tumor resection (p = 0.009), especially in patients up to 25 years of age (RR = 6.1; 95 % CI: 1.8–20.9; p = 0.004). The cases of recurrent AF were altogether significantly smaller than the primary tumors (p = 0.001). Post-treatment subcutaneous and muscle edema were present in 77 % and 56 %, respectively. Patients with muscle edema after primary tumor resection had a significantly higher risk for AF recurrences (relative risk ratio (RR) = 1.8; 95 % CI: 1.16–2.8; p = 0.0096). There was no significant difference detected in patients with complete or incomplete resection of the primary tumor.Conclusion Primary and recurrent aggressive fibromatosis has a mostly fascicular configuration, but may appear ovoid, nodular, streaky/flat or polycyclic as well. High risks for tumor recurrences are detected for patients up to 25 years of age, patients within the first 9 post-operative months and patients with muscle edema after primary tumor resection.Key points: Citation Format
Keywords: aggressive fibromatosis; configuration; MRI; risk factors; recurrence; post-treatment